Pengaruh Penggunaan Teknologi dan Insentif Terhadap Kinerja Karyawan Bagian Produksi di Pabrik Bumbu PT Abrofood Prima Makmur Kec. Pariaman Timur, Kota Pariaman - Nurofik, Agus; Pernanda , Syerli (Pustaka Galeri Mandiri, 2026)
The human resources play a crucial role in determining company performance, particularly in the production sector supported by the use of technology and incentive systems. However, limited mastery of technology, machine disruptions, and the suboptimal implementation of incentives can affect the achievement of employee performance. This condition also occurs at PT Abrofood Prima Makmur, making it necessary to conduct a study to examine the effect of technology utilization and incentives on the performance of production employees. This study employed a quantitative method with a population of 90 employees of PT Abrofood Prima Makmur. The sampling technique used was purposive sampling with the Slovin formula, resulting in 47 samples. The research data consisted of primary data collected through questionnaire distribution, which were tested for validity and reliability. Data analysis was conducted using multiple linear regression, classical assumption tests, t-test, F-test, and coefficient of determination with the assistance of SPSS version 26. The results show that technology utilization and incentives, both partially and simultaneously, have a positive and significant effect on employee performance, with a significance value of 0.000 < 0.005. The R² value of 0.537 indicates that these two variables explain 53.7% of employee performance, while the remaining 46.3% is influenced by other factors not examined in this study.